The Association Between Serum Palmitic Acid and Thyroid Function - Zhou, Guowei; Xu, Yumeng; Zhai, Yuqing; Gong, Zhen; Xu, Kun; Wang, Gaoyuan; Sun, Chenhua; Ma, Chaoqun (Frontiers in Endocrinology, 2022)
Aim: Emerging evidence indicates that palmitic acid (PA) can regulate the progression and development of many diseases. However, the study examining the association between PA and thyroid function remains sparse. We aimed to investigate the association between serum PA (sPA) and thyroid function in the US population. Methods: In this retrospective study, a cross-sectional analysis was performed using the data pooled from the database of the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2012. The thyroid parameters investigated were mainly free triiodothyronine (FT3), free thyroxine (FT4), total T3 (TT3), TT4, thyroglobulin (Tg), thyroid-stimulating hormone (TSH), anti-thyroglobulin antibody (TgAb), and anti-thyroperoxidase antibody (TPOAb). The central sensitivity to thyroid function was evaluated by the thyroid feedback quantile-based index (TFQI), thyrotrophin thyroxine resistance index (TT4RI), and thyrotropin index (TSHI). The FT3 to FT4 ratio (FT3/FT4) was employed to evaluate peripheral sensitivity to thyroid hormones. Multiple imputation was applied to handle the missing data, and weighted multivariable linear regression, subgroup, and interaction analyses were then employed to estimate the association between sPA and thyroid parameters. Results: In the 737 adults, after adjusting covariates, we demonstrated a significant negative association between sPA and FT4 [β = -1.078, 95% confidence interval (CI): -1.729 to -0.427], as well as a positive relationship between sPA and FT3/FT4 ratio (β = 0.073, 95%CI: 0.044 to 0.102), and these results did not change on multiple imputation. In the subgroup analyses, the associations were more significant in male and obese subjects. Conclusion: This investigation demonstrated the significant correlation between sPA and thyroid dysfunction, which suggested the close relationship between lipotoxicity and hypothyroidism or subclinical hypothyroidism. Future researches are required to confirm these findings.